A critical review of literature on the expected roles of principals in schools,Managing change at a South African Senior Secondary School : a case study,Situational analysis of my organisation with regard to organisational structure, leadership, decision making, communication and interpersonal relationships - Madaza, Simbongile Simphiwe (Rhodes University, Faculty of Education, Department of Education, 2002)
Schools, like all organizations, are undergoing radical changes in the way that their business is conducted. "One of the most significant of these is that leadership, rather than management, needs to be seen as the most crucial focus for institutional development and growth in the years ahead," (Whitaker, 1993). In these projects I focus on three dimensions of leadership. First, a critical review of literature on the expected roles of principals in schools. Second, a case study of change management at a South African senior secondary school; and finally, a situational analysis of my organization with regard to organizational structure, leadership, decision making, communication and interpersonal relationships.
Keywords: School principals -- South Africa; School management and organization -- South Africa; Educational change -- South Africa; Educational leadership -- South Africa